2001
DOI: 10.1300/j010v32n03_01
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Planning and Social Work Practice

Abstract: Current health care practice discharge planning has emerged as a major professional function in hospital settings. To examine the tasks involved in discharge planning and how frequently they are being performed, 124 Alabama hospitals were contacted with a 72% rcsponse rate. Of the 178 surveys returned by discharge planners the core tasks were identified and ranked in terms of performance frequency. The results revealed that the tasks performed typically resembled that of generalist social workers. When special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Moreover, managed care environments have forced professions to establish more specializations. According to Holliman, Dziegielewski, and Datta (2001), social workers in hospitals face many challenges, together with providing biopsychosocial needs; discharge-planning skills have become specializations in different health care settings.…”
Section: Social Work In Acute Health Carementioning
confidence: 99%
“…Moreover, managed care environments have forced professions to establish more specializations. According to Holliman, Dziegielewski, and Datta (2001), social workers in hospitals face many challenges, together with providing biopsychosocial needs; discharge-planning skills have become specializations in different health care settings.…”
Section: Social Work In Acute Health Carementioning
confidence: 99%
“…Further, when patient needs were not met, 25% of these patients were readmitted to the hospital one month and 24% three months post discharge. Although social work is at a disadvantage within the health care system because the services provided do not generally generate revenue for the hospital (Neuman, 2003), the array of HSW services such as counseling, communication, coordination, planning, and referral (Holliman, Dziegielewski, & Priyadarshi, 2001) are critical to overall resource usage (Burg et al, 2010;Lechman & Duder, 2006). In their hallmark study, Auerbach, Mason, and Laporte (2007) found that social work involvement contributed to cost-containment in hospitals.…”
Section: Principle 3: Individuals and Families Build On Their Strengtmentioning
confidence: 99%
“…In the narrative included in her research project, the student revealed the steps she took in working with the patient, the family, and the interdisciplinary team to guide service delivery. The student first established a standard of care based on the literature pertaining to discharge planning (Fox, 1996;Holliman, Dziegielewski, & Datta, 2001;Kadushin & Kulys, 1993;Kim & Moon, 2007). Using the literature as a foundation for creating a grid similar to the one shown above, she then analyzed her case notes and filled in the grid at the conclusion of her service delivery.…”
Section: Standardsmentioning
confidence: 99%
“…Second, it was determined that this student was able to meet the standard of efficiency in communication with team members to achieve a successful patient outcome. The student and field supervisor were able to connect the results to the literature that states that the key role of a hospital social worker is to communicate with the hospital team and translate this information into a timely and efficient discharge plan (Holliman et al, 2001). Feedback from the supervisor indicated that the process of using the standards-based comparison model was useful in evaluating whether the student demonstrated the aforementioned goal of using practice experience to inform scientific inquiry and research evidence to inform practice.…”
Section: Standardsmentioning
confidence: 99%